2015
DOI: 10.1021/acsnano.5b05814
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Random Lasers with Tunable Coherent Loops

Abstract: Stretchability represents a key feature for the emerging world of realistic applications in areas, including wearable gadgets, health monitors, and robotic skins. Many optical and electronic technologies that can respond to large strain deformations have been developed. Laser plays a very important role in our daily life since it was discovered, which is highly desirable for the development of stretchable devices. Herein, stretchable random lasers with tunable coherent loops are designed, fabricated, and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…For this purpose, several approaches for the control of random lasing modes had been proposed such as use of resonant scatterers [7][8][9][10][11], limiting excitation area [12,13], temperature control [14][15][16], tuning density of scatterers [17]. Among these approaches, it had been reported that changes in lasing modes were observed in random lasers fabricated on a soft substrate due to the structural changes induced by mechanically stretching the substrate [18][19][20], which has a merit of in situ tuning of lasing modes by adjusting the amount of bending or stretching the substrate. However, for maintaining the reproducibility and achieving the precise tuning, it is indispensable to use driving mechanism equipped with the structure, such as actuators.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, several approaches for the control of random lasing modes had been proposed such as use of resonant scatterers [7][8][9][10][11], limiting excitation area [12,13], temperature control [14][15][16], tuning density of scatterers [17]. Among these approaches, it had been reported that changes in lasing modes were observed in random lasers fabricated on a soft substrate due to the structural changes induced by mechanically stretching the substrate [18][19][20], which has a merit of in situ tuning of lasing modes by adjusting the amount of bending or stretching the substrate. However, for maintaining the reproducibility and achieving the precise tuning, it is indispensable to use driving mechanism equipped with the structure, such as actuators.…”
Section: Introductionmentioning
confidence: 99%
“…This result provides a strong evidence to support the fact that the density of Fe 3 O 4 NPs can be manipulated by the applied magnetic field. Our previous work also suggests that increasing scatterers density could lead to lasing with a shorter wavelength due to the decreasing cavity length . Besides, the influence of the magnetic field toward the threshold of the MCRLs has also been discussed and provided in Figure S6 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 93%
“…The tuning strategies of preprocess include modifying the absorption condition, the size of scatterers, and the geometry of photonic crystals . Besides, external parameters such as optics, electricity, temperature, and deformation, can realize wavelength tunability after the fabrication of disordered nanostructures, so called postprocess. Further, people drive persistent endeavors to control the random lasing modes.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent nanowires rationally fabricated into diverse shapes exhibit flexible photonic properties with respect to light propagation behavior and waveguide cavities, such as Fabry‐Perot and whispering gallery modes . Numerous semiconductor nanowires, including metal oxides and III‐V and II‐VI compounds with bandgaps ranging from ultraviolet to infrared, have also been considered.…”
Section: Nanowire Photonicsmentioning
confidence: 99%